ASSISTING STUDENTS’ WRITING IMPROVEMENT THROUGH READING TO LEARN (R2L) PROGRAM: A REVIEW OF STUDIES - Rahayu, Noviarti; Ningsih, Harni Kartika (English Review: Journal of English Education, 2023)
This paper aims to survey the implementation and the implication of Reading to Learn (R2L) for improving students' writing to inform future teaching practices. Reading to Learn (R2L) is a teaching methodology based on a language theory, Systemic Functional Linguistics (SFL), which has been reported as a successful program to improve students' literacy in different classroom contexts across the globe. This paper systematically reviews 14 studies on the implementation of R2L and its implications on students’ writing development from 2012 to 2023. This review indicates several key findings: 1) Most studies on R2L applied R2L to teach writing an argumentative genre, given that this genre is widely considered the most formidable genre for students; 2) The implementation of R2L exhibited various modifying strategies from the R2L cycles. Most studies modify the first layer of the cycles; 3) The final result shows the impact on students’ writing development. Thirteen out of the fourteen studies reviewed reported an increase in students’ textual organization, written literacy skills, students’ engagement in the classroom, and critical thinking.